Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Dan Kualitas Audit Terhadap Manajemen Laba - Viana Fandriani, Herlin Tunjung (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to discover whether the effect of profitability, leverage, firm size, and audit quality to earnings management. This research used purposive sampling method. The type of data is panel data during 2015-2017 in the form of data of property, real estate, and building construction obtained from Indonesia Stock Exchange with total sample was 153 data. Data analysis technique using multiple linear regression with Eviews (Economic Views) program 9.0. The results shows that leverage hassignificant positive efffect on earnings management, audit quality has significant negative effect on earnings management, meanwhile profitability and firm size have no significant effects on earnings management.